Patient-Centric Design of Topical Dermatological Medicines - Rita Oliveira; Isabel F. Almeida (MDPI AG, 2023)
Topical treatments are essential approaches to skin diseases but are associated with poor adherence. Topical vehicles have the primary purpose of ensuring drug effectiveness (by modulating drug stability and delivery, as well as skin properties) but have a marked impact on treatment outcomes as they influence patient satisfaction and, consequently, adherence to topical treatments. There is also a wide variety of vehicles available for topical formulations, which can complicate the decisions of clinicians regarding the most appropriate treatments for specific skin disorders. One of the possible strategies to improve topical-treatment adherence is the implementation of patient-centric drug-product design. In this process, the patient's needs (e.g., those related to motor impairment), the needs associated with the disease (according to the skin lesions' characteristics), and the patient's preferences are taken into consideration and translated into a target product profile (TPP). Herein, an overview of topical vehicles and their properties is presented, along with a discussion of the patient-centric design of topical dermatological medicines and the proposal of TPPs for some of the most common skin diseases.